Analysis Of The Principal's Transformational Leadership In Improving Teacher Performance At State Elementary School 2 Tanjung, Tanjung District - Muhammad Muzakkir; Musafir Musafir; Rauhun Jannah (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to describe the Analysis of Principal Transformational Leadership in Improving Teacher Performance at SD Negeri 2 Tanjung, Tanjung District. The main focus of this research, namely: (1) the transformational leadership style of the principal of SD Negeri 2 Tanjung in improving teacher performance.This research uses a qualitative approach with descriptive methods. Data collection techniques are done through observation, interviews, and documentation. Data analysis techniques using the Miles and Huberman Model. Transformational leadership style is characterized by the principal's ability to provide motivation, inspiration, individual attention, and encourage innovation in the school environment. The results of the study showed that the principal applied four main dimensions of transformational leadership, namely idealistic influence, inspirational motivation, intellectual stimulation, and individualized consideration. The application of this leadership style has a positive impact on improving teacher performance, which can be seen from the increase in discipline, responsibility, professionalism, and active participation in school activities. This study concludes that transformational leadership style is effective in creating a conducive work environment and encouraging improved teacher performance at SD Negeri 2 Tanjung.